2013
DOI: 10.1002/ejic.201201524
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Synthesis of Mesoporous Rare Earth Oxide Thin Films through Amphiphilic Ionic Block Copolymer Templating

Abstract: A new concept to achieve the generalized synthesis of crystalline mesoporous rare earth (RE) oxide thin films templated with an ionic amphiphilic block copolymer is developed. thin films as representatives of the light and heavy RE groups are synthesized by using polystyrene-block-poly(acrylic acid) (PS-b-PAA) as a templating agent. The impact of the concentration of PS-b-PAA on the morphologies of the mesopores is investi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…[15,18,[20][21][22][23][24][25][26] However, to our knowledge, only few crystalline rare-earth sesquioxides with an ordered mesoporous structure have been reported so far. [27][28][29][30] Castro et al reported the synthesis and optical properties of Eu 2 O 3 and Y 2 O 3 . [28,29] They showed that both materials can be templated to produce mesoporous thin films, but the synthesis involved several different steps and was rather complicated and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,18,[20][21][22][23][24][25][26] However, to our knowledge, only few crystalline rare-earth sesquioxides with an ordered mesoporous structure have been reported so far. [27][28][29][30] Castro et al reported the synthesis and optical properties of Eu 2 O 3 and Y 2 O 3 . [28,29] They showed that both materials can be templated to produce mesoporous thin films, but the synthesis involved several different steps and was rather complicated and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…[30] SDA used produced materials with rather small repeat distances is not beneficial as it strongly limits the thermal stability of the materials. Nevertheless, this approach is the only one in the literature that tends to be of a more general nature.…”
mentioning
confidence: 99%
“…Xiao et al. chose a diblock copolymer of poly(styrene‐ b ‐acrylic acid) as a pore‐directing agent to synthesize a series of mesoporous RE 2 O 3 thin films with a pore size of about 11 nm . Brezesinski et al.…”
Section: Figurementioning
confidence: 99%
“…[14] Xiao et al chose ad iblock copolymer of poly(styrene-b-acrylic acid) as ap ore-directing agent to synthesize as eries of mesoporous RE 2 O 3 thin films with ap ore size of about 11 nm. [15] Brezesinski et al reported an ew method to synthesize ordered mesoporous RE 2 O 3 thin films, in which poly(ethylene-co-butylene-bethylene oxide) (KLE)a nd poly(isobutylene-b-ethylene oxide) workeda sp ore-directing agentsa nd glacial acetic acid played ac rucial role in suppressing the recrystallization of RE 2 O 3 . [16,17] Use of the KLE template was also reported for the preparation of mesoporous Eu 2 O 3 thin films.…”
mentioning
confidence: 99%
“…In this block copolymer assisted synthetic route, the hydrolysis and condensation products of the organic precursors are preferentially incorporated into one of the blocks through hydrogen bonds. Accordingly, the morphology control of the corresponding functional inorganic part can be realized by phase separation behavior of the sol–gel solution . Templin and coauthors prepared a kind of organically modified aluminosilicate mesostructures from amphiphilic poly(isoprene‐b‐ethylene oxide) block copolymers.…”
Section: Introductionmentioning
confidence: 99%